2018 IEEE/CVF Conference on Computer Vision and Pattern Recognition 2018
DOI: 10.1109/cvpr.2018.00148
|View full text |Cite
|
Sign up to set email alerts
|

Bootstrapping the Performance of Webly Supervised Semantic Segmentation

Abstract: Bootstrapping the performance of webly supervised semantic segmentation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
77
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 31 publications
0
77
0
3
Order By: Relevance
“…CRF plays an important role to improve the accuracy of weakly supervised segmentation. Furthermore, various researches employed the CRF for refining the coarse segmentation masks [37,34,33,17,43,42,11,36]. However, CRF does not guarantee any improvement in the mean intersection over union (IoU) score, and it often degrades the segmentation masks and the scores.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…CRF plays an important role to improve the accuracy of weakly supervised segmentation. Furthermore, various researches employed the CRF for refining the coarse segmentation masks [37,34,33,17,43,42,11,36]. However, CRF does not guarantee any improvement in the mean intersection over union (IoU) score, and it often degrades the segmentation masks and the scores.…”
Section: Related Workmentioning
confidence: 99%
“…Motion segmentation of videos as additional training information for weakly supervised segmentation has also been proposed [39,10]. There are also reports that web images were helpful for improving the weakly supervised segmentation accuracy [30,43,16,36]. Recently, fully supervised saliency methods are being widely used for detecting the background regions, and certain researchers have reported that this approach could substantially boost performance [35,42,44,12,11,41,4].…”
Section: Related Workmentioning
confidence: 99%
“…Weakly supervised learning has been used in many areas of computer vision, e.g., image recognition [30], segmentation [16,32] and scene text detection [38,15], etc. Weakly supervised scene text detection methods [38,15] trained a supervised character-based detector using character-level bounding box and refined this model with word-level bounding box to improve the accuracy.…”
Section: Weakly and Partially Supervised Learningmentioning
confidence: 99%
“…Therefore, we propose a text reading model with partially supervised learning, which enables to train full and weak annotations in a unified model to keep it simple yet effective. Existing weakly supervised learning methods for image classification [30], segmentation [16,32] and text detection tasks [38] mainly focus on using image-level or bounding box as weak annotations, while end-to-end text reading aims to translate an image into a set of sequences, which is more challenging to solve. To address this problem, given only weak annotations in text labels without locations, we develop an Online Proposal Matching module (OPM) to select the best matched text proposals from weakly labeled images.…”
Section: Partially Supervised Learningmentioning
confidence: 99%
“…Combining weak annotations with small amounts of high-quality dense annotation is another strategy for reducing cost [9,26]. [52] proposes a two-stage approach where image-level class labels are automatically converted into pixel-level masks which are used to train a semantic segmentation network. We find a small number of sub-image block annotations is a competitive form of weak supervision (sec.…”
Section: Related Workmentioning
confidence: 99%